HUBUNGAN STATUS GIZI, KARAKTERISTIK INDIVIDU DENGAN PRODUKTIVITAS PEKERJA SORTING DAN PACKING - Rizqi Riyani Putri Farikha; Denny Ardyanto (Universitas Airlangga, 2016)
Good nutritional status affects physical and intellectual of activeness, productivity and veracity. Performance reaches of productivity in the mid-twenties and it declines with ages. Experience increases exponentially with tenure, and it can be seen from the level of educational attainment and skills. The objective of this study is to investigate relationship nutritional status, individual characteristics with productivity of sorting and packing employees of PT. DPG Muliakeramik Group. Primary and secondary data were employed as the source of data. The data were then processed and analysed descriptively. This research was observational and included field research with cross sectional design. Population of this study were sorting and packing employees of PT. DPG Muliakeramik Group with the total of 14 employees, and total sampling was used as the sampling method of this study. Nutritional status data were obtained from direct IMT. Interview with company’s representatives was taken to obtain information about individual characteristics (ages, tenure and education level) and workforce productivity. The collected data were then analysed using cross tabulation. The results indicated that most respondents have normal nutritional status (IMT). Most respondents were aged 26-35 years old with less than 6 years tenure, and most of them were graduated from Senior High School. The results of this study also indicated that most respondents have above average productivity. There is no relationship tenure, educational level with workforce productivity. This study is suggested that PT. DPG Muliakeramik Group could adjust workplace nutrition and give nutritional counselling for employees about the importance of consuming balanced nutrition.Keywords: nutritional status, individual characteristics, productivity